2013
DOI: 10.1371/journal.pbio.1001495
|View full text |Cite
|
Sign up to set email alerts
|

A Safeguard Mechanism Regulates Rho GTPases to Coordinate Cytokinesis with the Establishment of Cell Polarity

Abstract: Gps1 provides a novel molecular polarity cue at the cell division site that guides Rho1- and Cdc42-dependent polarization during and after cytokinesis in budding yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…Although haploid rga1D cells polarize preferentially at the division site [34], we found that diploid rga1D/ rga1D mutants retained a bias to polarize away from the division site. A very recent study identified a new Cdc42 antagonist present at the division site that collaborates with Rga1 to prevent budding at that site [42]. Modelling a situation with two uneven patches, competition was more effective and our simulations did evolve towards a single polarity site.…”
Section: (D) Localized Rsr1 -Gef Could Interfere With Competitionmentioning
confidence: 78%
“…Although haploid rga1D cells polarize preferentially at the division site [34], we found that diploid rga1D/ rga1D mutants retained a bias to polarize away from the division site. A very recent study identified a new Cdc42 antagonist present at the division site that collaborates with Rga1 to prevent budding at that site [42]. Modelling a situation with two uneven patches, competition was more effective and our simulations did evolve towards a single polarity site.…”
Section: (D) Localized Rsr1 -Gef Could Interfere With Competitionmentioning
confidence: 78%
“…This Rga1 localization is also likely to contribute to fluctuation of the Cdc42 cluster during T1 because the displacement of the Cdc42-GTP cluster is diminished in rga1Δ cells. Interestingly, Aim44/Gps1, which also prevents re-budding at the previous bud site, localizes to the division site as a disk (rather than a ring) (Meitinger et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The site of bud emergence (bud neck) will later be used in cytokinesis to separate the daughter from mother cell ( Figure 1A) (Park and Bi, 2007;Wloka and Bi, 2012). The remnants of the cytokinetic machinery (bud scar or cytokinesis remnant [CRM]) are retained in the mother cell and can be visualized by transmission electron microscopy (TEM) or by specific dyes ( Figure 1B) (Meitinger et al, 2013). CRMs mainly consist of extracellular matrix, which is encircled by a chitin-rich ring (Cabib et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Different GTPase-activating proteins (GAPs) contribute to the inhibition of Cdc42 at the cell-division site (Atkins et al, 2013;Tong et al, 2007). In addition, the scaffold protein Gps1 inhibits Cdc42 at the site of cytokinesis as part of a pathway working in parallel to the Cdc42 GAP Rga1 (Meitinger et al, 2013). However, neither Cdc42 GAPs nor Gps1 accumulate at old CRMs.…”
Section: Introductionmentioning
confidence: 99%